Nitrogenation of Amorphous Silicon : Reactive Molecular Dynamics Simulations - Mauludi Ariesto Pamungkas; Choirun Nisa; Istiroyah Istiroyah; Abdurrouf Abdurrouf (The Journal of Pure and Applied Chemistry Research, 2019)
Since silicon nitride (SiNx) film is more stable than SiO2, silicon nitride, thus it is widely used in semiconductor industry as an insulatorlayer. The study of nitrogenation process of a-Si was performed using molecular dynamics simulations to determine the properties of the bonds created in the structure of a-SiNx. Reactive force field (Reaxff) was used as potential in this molecular dynamic simulation owing to its ability to describe charge transfer as well as breaking and formation of atomic bonds. The structure of a-Si is obtained by melting the crystalline silicon at temperature of 3500 K followed by quenching to room temperature. The nitrogenation process was carried out by randomly distributing 900 N atoms over the a-Si surface for 60 ps at temperature varied from 300 K, 600 K, 900 K, and 1200 K. The higher the temperature nitrogenation applied in the system, the more number of N atoms adsorbed, resulting in a deeper penetration depth of Nitrogen atom. Amorphization and nitrogenation changed the distribution of coordination number of Ni, Si, and O atoms. Transfer of electrons from silicon to nitrogen occurs only in the nearest nitrogen atom with silicon atom.